Transnationalism and the Systemic Challenges of Peace in the Global South. Book Review: La cooperación internacional e intervención en escenarios de posconflicto (2020, Quintero) - Arroyo-Quirós, Joshua Steven (2023)
The book analytically compares the postconflict scenario in Colombia after the peace agreement in 2016  with the postconflict experiences in Rwanda by the end of the last century and the context of international cooperation and intervention in post-conflict Guatemala. In these cases, Transnationalism (focused on UN actions) is explicit in international cooperation for multidimensional and multifunctional reconstruction of these societies.